Long‐Term Effects of Repeated Cycles of Intrathecal Triamcinolone Acetonide on Spasticity in MS Patients. (20th November 2015) - Rommer, Paulus Stefan; Kamin, Frank; Abu‐Mugheisib, Mazen; Koehler, Wolfgang; Hoffmann, Frank; Winkelmann, Alexander; Benecke, Reiner; Zettl, Uwe Klaus
Summary: Main problem: Spasticity is a common feature in patients with multiple sclerosis (MS). Although options have broadened over the last years, there are still patients with no response to common therapeutic agents. Intrathecal administered triamcinolone acetonide (TCA) has been tested for spasticity in patients with MS. However, the long run effects are not known so far. The aim of this study was to evaluate the effects of repeated cycles of intrathecal TCA instillations on clinical parameters. Methods: A total of 54 patients with clinically definite MS and no response to commonly utilized antispastic drugs were enrolled. TCA was administered every 3 months for a period of 9 months. Clinical assessments including spasticity, disability (EDSS), mobility (walking distance, and timed 25‐foot walk), bladder function, and quality of life were carried out prior to and at the end of each treatment cycle. Results: Repeated TCA treatment led to repeated effects on spasticity ( P < 0.01). Bladder function improved in every 10th patient. Quality of life improved during each cycle but did not reach significance at the end of study ( P = 0.09). However, long‐lasting improvement on spasticity or EDSS was not shown at end of the study. Effects diminished over 3 months. Conclusion: Repeated TCA instillations led to replicable effects on spasticity; subgroup analyses suggest that higher spasticity, more frequent treatments, and higher EDSS may lead to pronounced effects on spasticity and EDSS. Intrathecal TCA treatment was safe and no severe side effects occurred. We hypothesize a significant time dependence of re‐administration of TCA and that an interval of 3 months between the treatments might be too long.